Design of aperture-coupled microstrip antenna for differential operation - Poh, Zhi Yong (Nanyang Technological University, 2021)
This document presents the overview of the FYP project “Aperture-Coupled Microstrip Antenna”. The student was assigned the project Aperture-Coupled Microstrip Antenna done under the supervision of Associate Professor Zhang Yue Ping. It describes the design and the simulation of a differentially- driven aperture-coupled microstrip antenna using aperture coupled feed technique. The design consists of three-layer structure: transmission feeding lines at the bottom of the feeding substrate, the ground plane with slot (aperture) at the mid layer and the radiating patch on the top of the radiating patch. The end objective of the project was to design a differentially-driven aperture-coupled microstrip antenna which gives advantages of lower noise and wider bandwidth.[1] It starts with a concise introduction of the project background, followed by the project objectives and goals. I will explain the skills and knowledge that are required to develop the project and my strategy to tackle